IDENTIFIKASI KARAKTERISTIK PERMUKIMAN KUMUH DI SEKITAR TAMAN MACCINI SOMBALA KOTA MAKASSAR - Rahayu, Irma; Jaharuddin, Wahyuni Ayu (Teknosains: Media Informasi Sains dan Teknologi, 2020)
Slum area is an area with a high population density in a city that is generally inhabited by poor people. Slums can be found in various major cities in the world. Slums are generally associated with high levels of poverty and unemployment. The rapid development of urban settlements is caused by population growth and urbanization which has resulted in slums. One of the slums in Makassar is located on Jl. Maccini Kelurahan Maccini Sombala, Makassar City. Residents who live in groups and build houses without thinking about space for housing support facilities. The houses in this settlement are semi-permanent and not permanent. Most are in the form of houses on stilts with very limited infrastructure, such as lack of road facilities, environmental drainage, clean water, waste water, and solid waste. The level of income of the population is very low where most residents work as fishermen, small traders, and artisans. The purpose of this study was to identify the characteristics of slums in Maccini Sombala Village. The benefits of this research are input for the Regional Government and the local community to formulate slum reduction policies, develop slum settlement structuring strategies by reviewing current conditions and alternative structuring in the future. From the results of primary and secondary data acquisition, the author uses a qualitative analysis method that is describing the data which is then followed by interpretation and conclusions. Presentation of data descriptively is by explaining, describing, and solving problems that are closely related to this research. The results of identification of residential buildings, the technical requirements of the building is known that 81% of buildings are not in accordance with the requirements in terms of safety, comfort, and health and 19% of livable buildings (according to building standards).